(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The prompt and remarkable development of nanotechnology has accompanied a great deal of interest in its use as a drug delivery procedure, anti-cancer, and bio-reducing agent. Therefore, this study was conducted at the Iraqi Center for Cancer and Medical Genetics Research for the period from 1-7-2021 to 15-1-2022 on cancerous and normal cell lines to assess the DNA damage. Comet Assay single-cell gel electrophoresis is a sensitive and versatile technique for measuring DNA damage and repair at the singlecell level, the genetic material of cancer cells. The biosynthetic nanoparticles were pretreated and measured by TEM. The nm20 nanomaterial created via the green technique was of a variety of sizes, allowing it to be stable and overcome challenges about nanoparticle toxicity. After extracting the active material from the basil plant using a GC-Mas instrument, the active substance was put onto silver. This study concluded that the biosynthetic material is effective for Michigan Cancer Foundation-7 (MCF-7) cells and safe for normal Human Foreskin Fibroblast cells (HFF) by evaluating the DNA damage by Comet Assay, making it an effective anti-cancer material.